Pengaruh Debt To Equity Ratio Terhadap Return On Asset Pada PT Sumber Alfaria Trijaya Tbk Tahun 2015-2025 - Violla Agatha; Marwan Setiawan; Adria Wuri Lastari (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2026)
This study aims to analyze the effect of the Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Sumber Alfaria Trijaya Tbk during the period 2015–2025. This research uses a quantitative approach with an associative method to examine the relationship between the independent and dependent variables. The data used are secondary data obtained from the company’s quarterly financial statements over the research period, with a total sample of 44 observations selected using a saturated sampling technique. The data analysis methods applied in this study include classical assumption tests to ensure the feasibility of the regression model, simple linear regression analysis to determine the direction and magnitude of the relationship between variables, t-test to examine the significance of the effect, and the coefficient of determination (R²) to measure the extent to which the independent variable explains the dependent variable. The results of the study show that the Debt to Equity Ratio (DER) has a negative and significant effect on Return on Assets (ROA). This is evidenced by a significance value of 0.000, which is lower than 0.05, and a t-statistic value of -8.469. The regression equation indicates that an increase in DER leads to a decrease in ROA. Furthermore, the coefficient of determination (R²) value of 0.631 shows that DER explains 63.1% of the variation in ROA, while the remaining 36.9% is influenced by other variables outside the model